Technological Provision for the Development of the Future Phychologists’ Self-Regulation of Situative Anxiety - Galieva, Olga (Psychological Prospects Journal, 2019)
The article explains the problem of the future practicing psychologists’ technological provision for situational anxiety. The technology of development of future psychologists’ self-regulation of situational anxiety has been determined as a complex system of technological procedures, aimed at reducing the level of manifestation of situational anxiety. We have proved that the theory of phased formation of mental actions (O. Leontiev, P. Galperin, D. Elkonin, N. Talizin and others) and the principle of social genesis of higher mental functions (L. Vygotsky) are the methodological basis for developing the technology of future psychologists’ self-regulation of situational anxiety. The basic stages of technology have been established as diagnostic, preparatory, basic, final (control) ones. The purpose of each of the stages is determined (the diagnostic stage is the identification of the level of manifestation of situational anxiety in the process; the preparatory stage – the activation of students, the provision of information on the methods of self-regulation of situational anxiety; students’ awareness of the need to reduce situational anxiety; the main stage is the external regulation of arbitrary actions regarding the use of situational anxiety self-regulation methods: with the help of a teacher; independently, when actions are accompanied by considerable willpower and a feeling of confidence; arbitrary regulation of actions in the process of applying the methods of self-regulation of situational anxiety; final (control) stage – re-determination of the level of occurrence of situational anxiety to determine the effectiveness of the technology). A technological map has been developed of the mechanism for the development of self-regulation of situational anxiety of future psychologists, where, in addition to the goal, the means and the expected result are determined at each stage of technology implementation. The essence of each stage has been sequentially disclosed. It is expected that in the process of consistent implementation of each stage, effective patterns of behavior will be formed in situations that may cause anxiety.